Absolute phase determination for low‐frequency ultra‐wideband synthetic aperture radar interferometry. Issue 2 (1st February 2016) - Xu, Junyi; An, Daoxiang; Huang, Xiaotao; Wang, Guangxue
Abstract : Absolute phase determination plays a key role in the synthetic aperture radar interferometry (InSAR). In this study, the authors focus on the low‐frequency ultra‐wideband (UWB) InSAR with large fractional bandwidth. They refer to the reference phase derived from the registration offsets as the registration phase (RP), and the subtraction of RP from the interferometric phase as the misregistration phase (MRP). Theoretical analysis shows that the MRP is inversely proportional to the fractional bandwidth of the synthetic aperture radar system and proportional to the misregistration. Therefore, for the UWB InSAR data, the MRP image is unambiguous in most of the area with high coherence, and phase unwrapping (PU) is even unnecessary for the MRP image when the fractional bandwidth is very large. Even though PU is required for the MRP image, it can be unwrapped efficiently by the classic minimum discontinuity PU algorithm since there are only a few discontinuities in it. Moreover, the residual ambiguity of the unwrapped MRP image can be estimated from the distribution of the unwrapped MRP. The proposed method is based on the above idea, and determines the absolute interferometric phase by adding RP and the obtained absolute MRP. The experimental results of the P‐band UWB InSAR data with fractional bandwidth of 0.25 demonstrate that the method is effective and more efficient than the traditional method.